2017
DOI: 10.1038/s41598-017-12987-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of telemedicine strategies on type 2 diabetes management: A systematic review and network meta-analysis

Abstract: The effects of telemedicine strategies on the management of diabetes is not clear. This study aimed to investigate the impact of different telemedicine strategies on glycaemic control management of type 2 diabetes patients. A search was performed in 6 databases from inception until September 2016 for randomized controlled studies that examined the use of telemedicine in adults with type 2 diabetes. Studies were independently extracted and classified according to the following telemedicine strategies: teleeduca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
142
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 44 publications
4
142
0
1
Order By: Relevance
“…Among the 118 included studies, Chrvala et al (2016) found that HbA1c levels were reduced with an average of −0.74%, which is comparable to our NMA findings of A1c levels [−0.73%; 95%CI −1.036, −0.414], when diabetes education was provided by health care team, which involved pharmacist as a team member. This was similarly noted in another study in which a healthcare team approach, which was delivered remotely could reduce HbA1c levels by 0.58% (Lee et al, 2017). …”
Section: Discussionsupporting
confidence: 58%
“…Among the 118 included studies, Chrvala et al (2016) found that HbA1c levels were reduced with an average of −0.74%, which is comparable to our NMA findings of A1c levels [−0.73%; 95%CI −1.036, −0.414], when diabetes education was provided by health care team, which involved pharmacist as a team member. This was similarly noted in another study in which a healthcare team approach, which was delivered remotely could reduce HbA1c levels by 0.58% (Lee et al, 2017). …”
Section: Discussionsupporting
confidence: 58%
“…Physicians use it, albeit rarely, in combination with telemetric information for clinical decision making. The decision making process is not based on any single value, such as may be the case in diabetes [60] as COPD patients are multi-morbid, elderly, with a particular social profile [57,61]. Comparing the three CLDs, some variables are present in all of them, while some are unique for a particular HCP.…”
Section: Discussionmentioning
confidence: 99%
“…Telesağlık uygulamalarının kan glukoz seviyesinin düzenlenmesini sağlayarak, hemoglobin A1c düzeyinin azalmasına katkıda bulunduğu belirtilmektedir. 40,41 Kronik hastalığı olan bireylere bakım verenlere yönelik hazırlanmış telesağlık uygulamalarının hasta, bakım verici ve sağlık profesyoneli arasındaki iletişimi artırarak, bakım vericilerin memnuniyetini ve konforunu, hasta ve bakım vericilere yönelik sosyal desteği artırdığı belirtilmektedir. 42,43 Videokonferansla verilen eğitimin hepatit C olan bireylerde tedavi maliyetini azalttığı, sağkalım süresi ve yaşam kalitesini artırdığı, hastalığa yönelik bilgi düzeyini artırdığı görülmektedir.…”
Section: Telesağlik Uygulamasi Sonrasinda Elde Edi̇len Sonuçlarunclassified